Reappraising the Tolosa‐Hunt Syndrome Diagnostic Criteria: A Case Series. Issue 1 (4th November 2019) - Mullen, Evan; Rutland, John W.; Green, Mark W.; Bederson, Joshua; Shrivastava, Raj
Abstract : Introduction: Tolosa‐Hunt syndrome (THS), a condition characterized by painful ophthalmoplegia and accompanied by cranial nerve palsies, remains as a diagnosis of exclusion. Nevertheless, the 3rd Edition of the International Classification of Headache Disorders (ICHD) has refined its diagnostic criteria to require the demonstration of granulomatous inflammation on magnetic resonance imaging or biopsy. We sought to assess the effectiveness of the new criteria in arriving at accurate diagnoses. Methods: We extracted all patient charts from our institution's electronic medical record associated with ICD‐9 code 378.55 (external ophthalmoplegia). We then completed the retrospective diagnostic workups to determine if subjects met ICHD‐3 criteria for THS and compared our findings with their final diagnoses. Results: Of 62 patients associated with ICD‐9 code 378.55, 10 (16%) was identified to have presenting symptoms concerning THS. The average age at the first onset of THS‐like symptoms was 58 years. Five of the 10 (50%) met ICHD‐3 criteria for THS. Two of the 5 (40%) meeting ICHD‐3 criteria for THS were discovered to have other diagnoses. Two of the 5 (40%) patients not meeting ICHD‐3 criteria for THS nevertheless received a final diagnosis of THS. Discussion: Our false‐negative rate of 40% is consistent with previous case series found in the literature. Our false‐positive rate of 40% is, to our knowledge, a new contribution to the literature as no other case series includes more than a single false‐positive. The false‐positive rate is most concerning, as a preliminary misdiagnosis of THS can delay treatment tailored to the true etiology. Furthermore, infectious etiologies can be exacerbated with steroid treatment. Conclusion: Our case series suggests that ICHD‐3 criteria are suboptimal for the accurate diagnosis of THS. We recommend a close follow‐up for all patients with symptoms concerning THS until a definitive responsible etiology is discovered and we encourage further studies assessing ICHD‐3 guidelines to optimize their sensitivity and specificity in the diagnosis of THS.